Diabetes and risk of occupational injury: a cohort study - Kouvonen A; Kivimaki M; Pentti J; Aalto V; Oksanen T; Virtanen M; Vahtera J (WILEY, 2022)
AimsTo investigate if diabetes is associated with a higher risk of occupational (workplace or commuting) injury.MethodsMedication data from the Finnish Prescription Register were used to identify diabetes cases in 2004 in a large employee cohort (the Finnish Public Sector study). These data were linked to injury records obtained from the Federation of Accident Insurance Institutions. A total of 1020 diabetes cases (median age 52 years, range 20 to 65 years; 66% women) and their 5234 age- and sex-matched controls were followed up until 2011. Sex-stratified Cox proportional hazards models, adjusting for age, occupational status, obesity and health behaviours, were applied. Because of the small number of men in the cohort, injury types and locations were only examined among women.ResultsDuring the median follow-up of 6.7 years, 25% of the participants with diabetes (n=252) and 20% of those without (n=1051) experienced an occupational injury. The association between diabetes and injury was stronger in women than men (P=0.048). Diabetes was associated with a higher risk of workplace (hazard ratio 1.37, 95% CI 1.11 to 1.69) and commuting (hazard ratio 1.36, 95% CI 1.03 to 1.79) injury in women. With regard to different injury types and locations, diabetes was associated with bone fractures, dislocations, sprains and strains, and injuries to upper and lower extremities. In men, there was an association between insulin-treated diabetes and commuting injury (hazard ratio 3.14, 95% CI 1.52 to 6.49).ConclusionsDiabetes was associated with workplace and commuting injuries in women. Men with insulin-treated diabetes had a higher risk of commuting injuries.